The Routledge international handbook of violence studies - DeKeseredy, Walter S., 1959-; Rennison, Callie Marie; Hall-Sanchez, Amanda K. (Routledge handbooks, 2019)
Violence is a serious public health problem. The number of violent deaths tells only part of the story, and many more survive violence and are left with permanent physical and emotional scars. Violence also erodes communities by reducing productivity, decreasing property values, and disrupting social services. In recent years, scholars have broadened their definitions of violence beyond the realm of interpersonal harms such as murder, armed robbery, and male-to-female physical and sexual assaults in intimate relationships, to include behaviors often ignored by the criminal justice system, such as human rights violations, racism, psychological abuse, state terrorism, environmental violations, and war. Guided by this broader definition of violence, this handbook offers state of the art research in the field and brings together international experts to discuss empirical, theoretical, and policy issues.